2018
DOI: 10.1158/0008-5472.can-18-0136
|View full text |Cite
|
Sign up to set email alerts
|

HER2/EGFR–AKT Signaling Switches TGFβ from Inhibiting Cell Proliferation to Promoting Cell Migration in Breast Cancer

Abstract: TGFβ signaling inhibits cell proliferation to block cancer initiation, yet it also enhances metastasis to promote malignancy during breast cancer development. The mechanisms underlying these differential effects are still unclear. Here, we report that HER2/EGFR signaling switches TGFβ function in breast cancer cells from antiproliferation to cancer promotion. Inhibition of HER2/EGFR activity attenuated TGFβ-induced epithelial-mesenchymal transition and migration but enhanced the antiproliferative activity of T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…HER2 is an important marker used in the diagnosis of breast cancer in women, while it is more and more frequently used for IHC tests in veterinary medicine (9)(10)(11). This receptor participates in the oncogenesis processes, by affecting cancer cell migration, increasing angiogenesis, and metastasis of cancer cells (9)(10)(11)44). In these published studies, there is no relationship reported between the intensity of the HER2 receptor expression and the level of PDPN expression in CAFs in mammary tumours in bitches.…”
Section: Discussionmentioning
confidence: 99%
“…HER2 is an important marker used in the diagnosis of breast cancer in women, while it is more and more frequently used for IHC tests in veterinary medicine (9)(10)(11). This receptor participates in the oncogenesis processes, by affecting cancer cell migration, increasing angiogenesis, and metastasis of cancer cells (9)(10)(11)44). In these published studies, there is no relationship reported between the intensity of the HER2 receptor expression and the level of PDPN expression in CAFs in mammary tumours in bitches.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies can be explained by differences in the mouse model experiment of methodology, mouse model age, antibodies and subject ethnicity in the studies (21). expression of Her1 is known to be closely associated with Her2 expression (24)(25)(26)(27). in breast cancer, Smad3, which can convert transforming growth factor-β into a carcinogenic factor, is activated when Her1 and Her2 are co-expressed, resulting in tumor progression (24).…”
Section: Discussionmentioning
confidence: 99%
“…expression of Her1 is known to be closely associated with Her2 expression (24)(25)(26)(27). in breast cancer, Smad3, which can convert transforming growth factor-β into a carcinogenic factor, is activated when Her1 and Her2 are co-expressed, resulting in tumor progression (24). The functional tyrosine domain of Her2 activates Her3 or Her1, promoting tumor development via activation of signaling pathways such as STaT3, raS-mitogen-activated protein kinase and Pi3K (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study elicits several unsolved issues that need further investigation. Firstly, as the crucial cytoplasmic signal transducers of TGF-β signaling, Smad2 and Smad3 have been indicated to exert different physiologic functions in different circumstances [1,[6][7][8]. Smad2 seems to have essential functions to mediate Activin/ Nodal signaling during embryogenesis, while Smad3 mediates TGF-β responses in adult tissues, such as growth inhibition, fibrotic responses in response to injury, synthesis of extracellular matrix proteins, immune suppression, EMT and cell migration [1,7,8].…”
Section: The Functional Switch Of Tgf-β Signaling In Breast Cancermentioning
confidence: 99%